The Magdalene in the Reformation - Arnold, Margaret 1973- (Cambridge, Massachusetts London, England The Belknap Press of Harvard University Press, 2018)
Introduction: A woman for all seasons -- The medieval Magdalene: establishing a cult of personality -- Teacher of the dear apostles: Lutheran preaching on Mary Magdalene -- Publish the coming of the Lord: evangelical Magdalenes -- A most holy penitent: preaching and teaching the Magdalene in the Catholic Reformation -- Love made her dare: the Magdalene among Catholic women -- These Magdalens: diversity in the reformed tradition -- Mark this, ye despisers of the weakness of women: the Magdalene of the Radical Reformation -- Conclusion: An army of such ladies
Prostitute, apostle, evangelist--the conversion of Mary Magdalene from sinner to saint is one of the Christian tradition's most compelling stories, and one of the most controversial. The identity of the woman--or, more likely, women--represented by this iconic figure has been the subject of dispute since the Church's earliest days. Much less appreciated is the critical role the Magdalene played in remaking modern Christianity. In a vivid recreation of the Catholic and Protestant cultures that emerged in the sixteenth and seventeenth centuries, The Magdalene in the Reformation reveals that the Magdalene inspired a devoted following among those eager to find new ways to relate to God and the Church. In popular piety, liturgy, and preaching, as well as in education and the arts, the Magdalene tradition provided both Catholics and Protestants with the flexibility to address the growing need for reform. Margaret Arnold shows that as the medieval separation between clergy and laity weakened, the Magdalene represented a new kind of discipleship for men and women and offered alternative paths for practicing a Christian life. Where many have seen two separate religious groups with conflicting preoccupations, Arnold sees Christians who were often engaged in a common dialogue about vocation, framed by the life of Mary Magdalene. Arnold disproves the idea that Protestants removed saints from their theology and teaching under reform. Rather, devotion to Mary Magdalene laid the foundation within Protestantism for the public ministry of women.--
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Mary Magdalene -- Saint; Mary Magdalene -- Saint -- Cult; Mary Magdalene; Mary Magdalene -- Cult; Women in Christianity -- Europe -- History; Women in Christianity -- History -- Europe; Reformation; Europe -- Church history -- 16th century; Europe -- Church history -- 17th century; Europe -- Church history -- 16th century; Europe -- Church history -- 17th century